Inside major East Asian library collections in North America. volume 2 - Lo, Patrick; Anghelescu, Hermina G. B.; Allard, Bradley (Emerald Publishing Limited, 2022)
As a branch of International and Area Studies Librarianship (IASL), East Asian Librarianship has become increasingly important in an age of globalization as scholars engage in interdisciplinary research and study. Volume 2 of Inside Major East Asian Library Collections in North America presents an extensive collection of interviews that give key insights into Chinese, Korean, and Asian American librarianship. East Asian Studies librarianship requires a variety of technical skills, combining deep subject background with knowledge of library processes/workflows, an awareness of research trends, and digital developments in their respective fields. Professionalism, tradition, standards, respected bodies of knowledge and individual practicing professionals' personality traits are closely examined over both volumes. Inside Major East Asian Library Collections in North America promotes shared understanding of subject area librarians' work and contribution to society and will enable further collaborations and new services, utilizing the unique and distributed nature of their expertise.